ADAM: a robotic companion for enhanced quality of life in aging populations - Mora, Alicia; Prados, Adrian; Mendez, Alberto; Espinoza, Gonzalo; Gonzalez, Pavel; Lopez, Blanca; Muñoz, Victor; Moreno, Luis; Garrido, Santiago; Barber, Ramon (Frontiers in Neurorobotics, 2024)
One of the major problems of today's society is the rapid aging of its population. Life expectancy is increasing, but the quality of life is not. Faced with the growing number of people who require cognitive or physical assistance, new technological tools are emerging to help them. In this article, we present the ADAM robot, a new robot designed for domestic physical assistance. It mainly consists of a mobile base, two arms with grippers and vision systems. All this allows the performance of physical tasks that require navigation and manipulation of the environment. Among ADAM's features are its modularity, its adaptability to indoor environments and its versatility to function as an experimental platform and for service applications. In addition, it is designed to work respecting the user's personal space and is collaborative, so it can learn from experiences taught by them. We present the design of the robot as well as examples of use in domestic environments both alone and in collaboration with other domestic platforms, demonstrating its potential.